OP12 Targeting inflammation in ulcerative colitis by inhibiting glucose uptake. (25th January 2019) - Gropp, R; Jodeleit, H; Caesar, J; Villarroel Aguilera, C; Beigel, F; Breiteneicher, S; Stallhofer, J; Siebeck, M
Abstract: Background: The energy supply of inflammatory cells relies on three sources: Glycolysis, oxidation of lipids, and amino acid (AS) metabolism. In homeostasis, when the major task of inflammatory cells is the maintenance of tolerance, lipids are the preferred source as lipid oxidation is the most efficient albeit slowest pathway to generate ATP: The response to an assault, however, requires the immediate activation, proliferation, differentiation of inflammatory cells, their migration to sites of inflammation and expression of cytokines, growth factors and chemokines. These processes demand prompt energy supply which is met by a metabolic switch from lipid oxidation to glycolysis to ensure swift ATP generation and the synthesis of biosynthetic intermediates albeit at the expense of efficiency. Therefore, the dependence on glycolysis might offer an Achilles' heel of inflammatory cells. Glucose uptake into the cell is regulated by the PI3K/AKT/mTOR pathway and glucose uptake transporters (GLUT). Therefore, we tested the PI3K inhibitor copanlisib and the glucose uptake inhibitor ritonavir in vitro and in vivo . Methods: Peripheral blood mononuclear cells (PBMC) were activated with anti CD3/CD28 in the presence of ritonavir. Cells were analysed by flow cytometric analysis. A seahorse analysis was performed. To examine the effect of ritonavir in vivo, the NSG-UC mouse model was used which is based on immunocompromised NOD-scid IL-2R null mice reconstituted with (PBMC) from patients with ulcerative colitis (UC). Dependent variables were clinical and histological score, frequencies of human leucocytes isolated from spleen and colon and levels of amino acids (AS) in sera of mice. Results: Frequencies of activated CD4+ cells (CD4+ CD69+, CD4+ CD134+) were significantly affected by ritonavir and copanlisib. Ritonavir affects frequencies of CD4+ T-cell subtypes. Copanlisib predominantly inhibited glycolysis induced by activation of CD4+ cells with anti CD3+ / CD28 antibodies and activation of monocytes induced by LPS. Mice benefited from treatment with ritonavir as indicated by decreased clinical ( p = 0.05) and histological ( p = 7e−0.5) scores and Glu levels ( p = 0.02). PCA analysis revealed a clustering of ritonavir treated mice with control mice. Principal component analysis discriminates between the control group, ethanol-challenged group and ritonavir-treated group. Conclusions: Targeting metabolic pathways might open up new avenues for therapeutic interventions. Patients might benefit from FDA-approved drugs as copanlisib or ritonavir.